2007
DOI: 10.1002/job.477
|View full text |Cite
|
Sign up to set email alerts
|

Externalization of employment in a service environment: the role of organizational and customer identification

Abstract: SummaryThis study investigates the impact of employment externalization (in the form of limited-term vs. permanent employment status) on customer-oriented service behavior, and how identification processes may help to resolve the 'paradox of externalization' (i.e., organizations relying more on potentially disenfranchised employees to maintain strong connections with their customers). Survey data were obtained from 369 sales, service, and technical support personnel from the Canadian subsidiary of a large inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 70 publications
3
58
0
1
Order By: Relevance
“…Research has also found poorer customer service associated with contract service workers. In a study of service workers, compared to permanent status employees, workers on a two-year contract were found to be less customer-oriented, due to their lower levels of organizational identity and customer identification ( Johnson & Ashforth 2008). Contractors with family constraints around working time were less successful than those without constraints (Vincent 2016).…”
Section: Wwwannualreviewsorg • Two Images Of the New World Of Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Research has also found poorer customer service associated with contract service workers. In a study of service workers, compared to permanent status employees, workers on a two-year contract were found to be less customer-oriented, due to their lower levels of organizational identity and customer identification ( Johnson & Ashforth 2008). Contractors with family constraints around working time were less successful than those without constraints (Vincent 2016).…”
Section: Wwwannualreviewsorg • Two Images Of the New World Of Workmentioning
confidence: 97%
“…Created to enable firm agility in labor markets, this dimension of flexibility shifts work from standard employment to shorter-term work assignments ( Johnson & Ashforth 2008), often leading to feelings of job insecurity (Lam et al 2015). We focus on three specific categories in the Cappelli & Keller (2013) classification scheme where research has been conducted in the past decade: direct employment beyond the standard employment relationship, co-employment/agency work, and contracting.…”
Section: Flexibility In the Employment Relationshipmentioning
confidence: 99%
“…Hence, we initiate a necessary, albeit an ignored, scholarly debate by suggesting that the CSR profile of the firm may be one tool that can be utilized to alleviate the negative impact of externalization on irregular workers. Finally, we prove our hypotheses by focusing on an employee group that faces the acutest form of externalization, that is, subcontracted workers (Johnson & Ashforth, ).…”
Section: Hypotheses Developmentmentioning
confidence: 83%
“…Fourth, our focus on subcontracted workers underscores our intent to prove our hypotheses in a complex three‐way work arrangement (Drucker & Stanworth, ) representing the most extreme form of irregular employee externalization (Johnson & Ashforth, ). Finally, we test our model in the collectivistic culture of South Korea .…”
Section: Introductionmentioning
confidence: 94%
“…In most cases, construction workers are temporarily employed for this specific task in the project, and move to another project after completing their tasks. This condition of temporary employment can undermine workers' social identification with the organization (Johnson andAshforth 2008, Buonocore 2010), and under such circumstances greater in-group identification could be expected (van Rijswijk et al 2006). Previous research has found that social structures at work can foster a stronger identification with the workgroup than with the organization as a whole (Hennessy andWest 1999, Löwstedt andRäisänen 2014).…”
Section: Discussionmentioning
confidence: 99%